A facile green synthesis route to silver nanoparticles using cyanobacterium Nostoc carneum and its photocatalytic, antibacterial and anticoagulative activity. (March 2023) - Borah, Debasish; Das, Neeharika; Sarmah, Pampi; Ghosh, Kheyali; Chandel, Madhurya; Rout, Jayashree; Pandey, Piyush; Ghosh, Narendra Nath; Bhattacharjee, Chira R.
Abstract: A facile green synthesis method for the synthesis of silver nanoparticles (AgNPs) using dried biomass of a cyanobacterium, Nostoc carneum has been developed by reduction of aqueous solution of silver nitrate. The as-synthesized silver nanoparticles were characterized using ultraviolet-visible (UV-Vis) spectrophotometry, transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX) and dynamic light scattering (DLS) studies confirmed the formation of polydispersed, quasi-spherical shaped silver nanoparticles with 4–22 nm size stable beyond ∼90 days. Fourier transform infrared (FTIR) analysis indicated the presence of phytochemicals on the AgNPs surface which served as both reducing and capping agents. The powder X-ray diffraction (XRD) study indicated a face-centered cubic crystalline structure of the nanoparticles. The as-synthesized silver nanoparticles exhibited a rather high photocatalytic activity for the degradation of two water soluble dyes, methylene blue (MB) and 2-Nitroaniline (2-NA) with degradation efficiency 92.5% and 82.5%, respectively. Kinetic study of the degradation reaction revealed the rates to be pseudo-first order in nature with rate constants 0.1138 min −1 and 0.0443 min −1 for MB and 2-NA, respectively. Significant antibacterial activity of the AgNPs against four selected pathogenic bacterial strains was observed. Further, the phytomolecule loaded AgNPs exhibited anticoagulant activity by inhibiting the human blood clotting for > 4 h. Graphical Abstract: ga1